2015
DOI: 10.4047/jap.2015.7.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentin pretreatment and curing mode on the microtensile bond strength of self-adhesive resin cements

Abstract: PURPOSEThe aim was to evaluate the effect of curing mode and different dentin surface pretreatment on microtensile bond strength (µTBS) of self-adhesive resin cements.MATERIALS AND METHODSThirty-six extracted human permanent molars were sectioned horizontally exposing flat dentin surface. The teeth were divided into 12 groups (3 teeth/group) according to the dentin surface pretreatment methods (control, 18% EDTA, 10% Polyacrylic acid) and curing mode (self-curing vs. light-curing) of cement. After pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
1
20
0
5
Order By: Relevance
“…Because RelyX U200 resin cement has higher filler content and viscosity, primer application to zirconia increased its wettability and allowed easier penetration of the resin cement [ 30 ]. Another study also reported that primer application dramatically increases the bond strength when RelyX U200 is used [ 31 ]. This is consistent with previous studies [ 27 , 32 ] and shows that both air-abrasion and primer application contribute to effective bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Because RelyX U200 resin cement has higher filler content and viscosity, primer application to zirconia increased its wettability and allowed easier penetration of the resin cement [ 30 ]. Another study also reported that primer application dramatically increases the bond strength when RelyX U200 is used [ 31 ]. This is consistent with previous studies [ 27 , 32 ] and shows that both air-abrasion and primer application contribute to effective bonding.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has pointed that the biomechanical behavior of self-adhesive resin cements is affected by their interaction with the dentin [19]. Hattar et al [4] compared the bonding strength of three different self-adhesive cement trademarks.…”
Section: Discussionmentioning
confidence: 99%
“…Low bonding strength values were found, notably because the selfadhesive resin cements did not dissolve the smear layer, only superficially infiltrated the collagen fiber network [4]. Youm et al [19] suggested that scrubbing the dentin with 18% EDTA or 10% polyacrylic acid before cementation could significantly increase the micro tensile strength of these cements. In the present case, 18% EDTA solution was used, followed by neutralization with sterile saline solution, previously to the post cementation.…”
Section: Discussionmentioning
confidence: 99%
“…Fatores como utilização de clorexidina 2% ou agentes quelantes como tratamento de superfície, influencia de materiais cimentantes provisórios, influencia do tempo entre a manipulação, influência do modo de cura na energia de superfície também são fatores que influenciam diretamente no processo de cimentaçã [13][14][15] .…”
Section: Revisão Da Literaturaunclassified
“…Youm et al 13 avaliaram o efeito do modo de cura e diferentes pré-tratamentos na resistência a microretenção dos cimentos autoadesivos. Concluíram que com o RelyX U200 o pré-tratamento com EDTA ou ácido poliacrílico pode ser recomendada para aumentar a resistência de união do cimento à dentina.…”
Section: Revisão Da Literaturaunclassified